The Importance of Character Education in the World of Education at Primary School of 177675 Sigordang - Devi Melati Winarti Hutapea; Nova Yunita Sari Siahaan; Dapot Tua Manullang; Juliwati Batubara; Hepmida Simanjutak (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2022)
Teaching Campus Program Batch III which is one form of implementation of the Independent Learning Campus Merdeka (MBKM) in the form of teaching assistance to empower students in helping the learning process in elementary schools in various villages/cities, one of which is at SD Negeri 177675 Sigordang which is located at Sigordang, Siantar Narumonda District, Toba Regency, North Sumatra. In this program, the students involved are responsible for assisting the school in the teaching process, assisting with technology adaptation, and assisting with administration. In addition, students have a responsibility to improve student character and increase student interest in learning during this pandemic. The results of this program are as an inculcation of empathy and social sensitivity in students towards the problems of community life around them; hone thinking skills in working together across fields of science and students' various origins in solving problems they face; develop students' insight, character and Soft Skills; encourage and spur national development by fostering community motivation to participate in development; as well as increasing the real role and contribution of universities and students in national development.